PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN MAHASISWA MEMILIH FAKULTAS EKONOMI UNIVERSITAS YARSI - La Diadhan Hukama; Zainal Zawir Simon (Universitas Muhammadiyah Metro Lampung, 2018)
The purpose of this research is to examine the impact of service maketing mix on student’s decision toward university choice. The objectives were: to determine factors of service marketing mix that affect student’s decision making and which factors are significantly affected it. The samples were students of Economic Faculty of YARSI University.The results of the research showed that there is only three factors from service marketing mix that significantlyhave an influence on the students’ decision. Those three factors were product(sig = 0.000), promotin, (sig = 0.042) and physical evidence (sig = 0.001), while price and place do not influence on the students’ decision. Key words: marketing mix services, students’ decision.